A randomized trial of vaginal misoprostol for cervical priming before hysteroscopy in postmenopausal women - Anita Kant; Divyakumar; Usha Priyambada (Wolters Kluwer Medknow Publications, 2011)
Objective: To perform hysteroscopy the cervix needs to be dilated and in nullipara and postmenopausal women this is sometimes difficult. Well-known, entry-related complications during hysteroscopy include cervical tear, creation of false tract, bleeding, uterine perforation, scarring, and subsequent anatomical stenosis. Materials and Methods: This study was done to investigate the priming effect of vaginal misoprostol on cervical dilatation in postmenopausal women, before hysteroscopy, to prevent such complications. Two hundred micrograms of misoprostol was inserted into the vagina at least 12 hours before the procedure and the control group did not receive any cervical priming agent. Pre-procedural dilatation, additional dilatation required, and time taken for dilatation was noted in each case. Observations: The study showed a significant difference between the study group (7.7 ± 1.7 mm) and the control group (4.5 ± 1.8 mm) in terms of pre-procedural cervical width and the number of women requiring a dditional dilatation (7 / 25 versus 22 / 25), and hence, the time required for dilatation (4.7 ± 8 seconds versus 20.6 ± 9.3 seconds). Conclusion: The pre-procedural cervical width was significantly more in the study group as compared to that in the control group. We found significant differences between the study and control groups with respect to the number of women who required cervical dilatation. To conclude, this study helps derive a conclusion that vaginal misoprostol as a cervical priming agent in postmenopausal women appears to be safe, effective, and inexpensive, with mild side effects.